Designing decision pathways for diabetes self-care management for individuals living with diabetes in Nabunturan, Davao de Oro - Abella, KC Ann Neljane P. (2023)
The applied nature of health communication research is firmly rooted in the implicit goal of facilitating improvements in care delivery and health promotion to improve health outcomes. In fact, the recent, rapid advances in interactive digital technologies have significantly changed how health communication interventions are developed and implemented. In this study, a health communication intervention tool was developed to address the diverse needs and challenges of the individuals living with diabetes in Nabunturan, Davao de Oro in managing their condition. Through the theme identification grounded by social cognitive theory, it revealed the different factors that influenced the decision-making process of the individuals in their diabetes care and management. The production process was grounded by the design thinking process to ensure the user experience of the digital decision pathways that is intended for the individuals living with diabetes in Nabunturan as well as their care providers. The key messages that surround the digital decision pathways centers on Reinforcing Self-Efficacy, Trust in the Healthcare Provider, the need for support from their social network, and the need to build financial capacity. More so, to ensure its effectiveness the digital decision pathways were pretested and fine-tuned.